2004
DOI: 10.1088/0953-8984/16/23/028
|View full text |Cite
|
Sign up to set email alerts
|

The orthorhombic to tetragonal phase transition in Bi1.75Te0.25SrNb1.75Hf0.25O9

Abstract: The necessity to produce materials with better performances than those observed in ferroelectric perovskites has generated the creation of new oxides, especially those belonging to the Aurivillius family. In the last few years much attention has been paid to the study of these materials, and this has opened up new fields due to their basic and applied properties. In this contribution a Raman analysis and a hyperfine study by perturbed angular correlations spectroscopy of Bi 1.75 Te 0.25 SrNb 1.75 Hf 0.25 O 9 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[16] Previous Raman spectroscopic studies on the nature of ferroelectricity in Aurivillius compounds have also demonstrated the interplay between the A-site cationic displacements and the FE-PE phase transition. [25,33,[47][48][49] As can be seen in Fig. 3, ω 42 (T) for both Mndoped compounds shows the same behavior as for Mn-free PbBi 4 Ti 4 O 15 .…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…[16] Previous Raman spectroscopic studies on the nature of ferroelectricity in Aurivillius compounds have also demonstrated the interplay between the A-site cationic displacements and the FE-PE phase transition. [25,33,[47][48][49] As can be seen in Fig. 3, ω 42 (T) for both Mndoped compounds shows the same behavior as for Mn-free PbBi 4 Ti 4 O 15 .…”
Section: Resultsmentioning
confidence: 67%
“…suggested that for Aurivillius compounds with a space group A 2 1 am , the displacements of the A ‐site cations in the perovskite blocks are strongly related to the major spontaneous polarization . Previous Raman spectroscopic studies on the nature of ferroelectricity in Aurivillius compounds have also demonstrated the interplay between the A ‐site cationic displacements and the FE–PE phase transition . As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 83%